2005
DOI: 10.1002/qua.20600
|View full text |Cite
|
Sign up to set email alerts
|

Is the vibrational optical activity of (R)‐[2H1, 2H2, 2H3]‐neopentane measurable?

Abstract: ABSTRACT:The compound, (R)-[ 2 H 1 , 2 H 2 , 2 H 3 ]-neopentane, with its T d symmetric electron distribution, is the archetype of molecules that owe their chirality exclusively to an asymmetric distribution of the masses of their nuclei. It has nine rotamers, which fall into two classes, one where the interchange of hydrogen and deuterium nuclei leads to an identical rotamer, and one where it interconverts different rotamers. Ab initio computations show that individual rotamers have Raman optical activity (RO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
0
8

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 38 publications
0
48
0
8
Order By: Relevance
“…1 is in terms of vibrational energy, with the volume of the spheres chosen proportional to the fraction individual nuclei contribute to the total energy of a vibration [39]. The ratio of the kinetic energy of nucleus α in vibration p to the vibration's total kinetic energy is given by…”
Section: Intramolecular Vibrationsmentioning
confidence: 99%
“…1 is in terms of vibrational energy, with the volume of the spheres chosen proportional to the fraction individual nuclei contribute to the total energy of a vibration [39]. The ratio of the kinetic energy of nucleus α in vibration p to the vibration's total kinetic energy is given by…”
Section: Intramolecular Vibrationsmentioning
confidence: 99%
“…As the invariants are proportional to (L x α,p ) 2 / ν p and, in turn, cross sections, the size of the spheres is further divided by the wave number ν p associated to vibrational mode p (except for VCD). 4 This option based on the sphere representation is implemented in pyVib.…”
Section: Representation Of Vibrations and Vibrational Energiesmentioning
confidence: 99%
“…4 Starting from the virial theorem and the harmonic approximation, the fractional energy can be written as…”
Section: Representation Of Vibrations and Vibrational Energiesmentioning
confidence: 99%
“…Haesler and colleagues' synthesis 1 of (R)-[ 2 H 1 , 2 H 2 , 2 H 3 ]-neopentane with high enantiomeric purity was itself an achievement, and was attempted only after calculations 8 suggested that the ROA might be measurable. It is a gas at room temperature, but was collected as a liquid for ROA measurements by distilling into a cooled capillary tube that was subsequently sealed.…”
mentioning
confidence: 99%
“…Haesler et al 1 simulated the ROA spectrum of the chiral neopentane using ab initio quantum-chemical protocols 8 . They summed the partially cancelling ROA spectra computed for each of the nine possible rotational conformers present at thermal equilibrium.…”
mentioning
confidence: 99%